Living, Caring, Learning – Listening to patients with bleeding disorders and not being afraid to advocate - Witkop Michelle (The Journal of Haemophilia Practice)
Michelle brought experience of working with people with chronic pain to her role as a bleeding disorders nurse, before going on to develop a research department at the National Hemophilia Foundation (now the National Bleeding Disorders Foundation). Reflecting on the pain experienced by various individuals she cared for, she highlights the importance of listening carefully to what patients have to say and the value of patient-reported information. Michelle explains how understanding this led her into patient advocacy, and how nurses acting as advocates for their patients supports their care and thereby enable people with bleeding disorders to live the best life they can.